DAMPAK KENAIKAN HARGA KEDELAI TERHADAP INDUSTRI TAHU DAN TEMPE DI KOTA PEKANBARU - Ningsih, Oktaria; Harahap, Azwar; Indrawati, Toti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in the Pekanbaru City with the object of research is businessman tofu and tempe which are in each district. The purpose of this study was to determine how the industry characteristics of tempe and tofu in Pekanbaru city, and to investigate the impact of rising soybean price to income derived tofu and tempe. Analysis of the data used is descriptive data analysis. Result of research conducted on 37 respondents note that thecharacteristics of the industry tofu in the Pekanbaru city is the industry intensive, is evidenced by the value of CLR highest amounted to only 30,30%, this means that the CLR has little value, so it can be concluded tha the industry tofu and tempe in Pekanbaru city is still quite labor-intensive industries. The increase in soybean prices affect the ability of artisans in the production, including the increase in selling price, lower revenue and a decrease in the operating income, change in shape in the production of tofu and tempe. The increase in soybean price make the revenues of businessman tofu decreased in once the production out of the income of Rp. 54.011.480 million after the price hike on soy tofu income decreased to Rp. 52.550.669. it can be concluded that the increase in soybean prices affect the industry tofu and tempe in Pekanbaru city.Keywords:Price, Soybean, Tofu, Tempe.